PEMIKIRAN A. MUKTI ALI (RELIGIUS-RASIONAL) TENTANG PENDIDIKAN ISLAM DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM KONTEMPORER - NURIAWATI NURIAWATI; MARAGUSTAM MARAGUSTAM (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2022)
This study aims to determine, understand and add insight into knowledge related to A. Mukti Ali's thoughts on Islamic education (religious-rational) and its relevance to contemporary Islamic education. The type of research used is qualitative through an analytical descriptive approach with scientific literature studies. The data are collected systematically in relevant articles, such as journals, books and documents that discuss significantly A. Mukti Ali's thoughts. The results of the study explain that A. Mukti Ali's educational thinking concepts are based on scientific concepts known as scientific-cum-doctrinaire, the concept of nationality is known as agree in disagreement, and the concept of humanity. With these three focuses of thought, A. Mukti Ali seeks to build human civilization and education through the results of the Decree of the Ministerial Decree of i3, namely the similarity in the degrees of graduates of public schools and madrasas. Which means A. Mukti Ali has initiated the concept of non-dichotomous education, the integration of educational values between religion, humans and society. So, these findings can be used as a reference for every human being, especially to be open about difference.